REPORTS FOR CREDITORS. - Drake, Milton J. (The Accounting Review, 1950)
The article focuses on the financial reports for creditors. Creditors are those individual or business organization which deliver goods , wares, or services, or lend their money, to a debtor in exchange for a promise to pay at some time in future. The creditor's confidence in receiving payment in the future is based upon the history, reputation, and character of the debtor, supported by adequate accounting reports. Accounting reports are the creditor's principal tool. They consist of reports of independent accountants, reports of management to stockholders, and special financial and statistical analyses. The factor which distinguishes the creditor from the stockholder or other groups is primarily the use to which he puts the reports, and the approach he takes to becoming or continuing to be a creditor. Creditors can be classified into three broad groups. First are the trade creditors who sell merchandise, materials or services to the debtor. Second are the bank creditor who lends money to the debtor on an institutional basis for more or less short periods. The third class of creditors is security holders, who lend money to the debtor for a long period of time.